1995
DOI: 10.1021/bi00048a026
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Escherichia coli Regulatory Protein TyrR and DNA: A Fluorescence Footprinting Study

Abstract: The Escherichia coli regulatory protein TyrR controls the expression of eight transcription units that encode proteins involved in the biosynthesis and transport of aromatic amino acids. It is a homodimer of 57 600 subunit molecular weight and has a binding site for ATP and weak ATPase activity. In the presence of ATP, TyrR binds tyrosine, which induces self-association of TyrR from a dimer to a hexamer. This report examines the interaction of TyrR with a 42 bp DNA oligonucleotide containing a centrally locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…In our study, the values of naked ODNs are relatively low as compared with those found by other groups (27)(28)(29). The origin of this discrepancy is not clear but our data show that the steady-state anisotropy is not proportional to the ODN length.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In our study, the values of naked ODNs are relatively low as compared with those found by other groups (27)(28)(29). The origin of this discrepancy is not clear but our data show that the steady-state anisotropy is not proportional to the ODN length.…”
Section: Discussioncontrasting
confidence: 92%
“…Other examples of protein-DNA complexes described in the literature display similar behavior. For TBP (27 kDa) and the TyrR homodimer (57.6 kDa), the values of the final protein-DNA complexes (8.5 and 28 ns, respectively) are similar to those predicted for the free proteins (27,28).…”
Section: Discussionsupporting
confidence: 69%
“…In a previous study, the association of TyrR protein with a 42 bp DNA duplex containing a fluorescein label adjacent to the protein-binding site also resulted in a significant fluorescence enhancement and an increase of anisotropy. 23 In that system, the fluorescence changes were attributed to contact between the protein surface and the fluorophore, and it is likely that the fluorescence behavior observed here is also the result of a direct interaction between the probe and the protein. This is somewhat surprising, because the fluorescein probe is attached to the 5 0 end of the primer strand, some distance upstream of the junction between the double and single-stranded regions of the primer/template where KF is expected to bind.…”
Section: Discussionmentioning
confidence: 74%
“…One such study with template/primer oligonucleotides, where a fluorescent dansyl probe was appended at various nucleotide positions from the 3 -end of the primer, indicated that the Klenow polymerase remains in contact with the template/primer up to six nucleotides from the 3 -end (238). Similarly, contacts between a 42-mer oligonucleotide and the E. coli regulatory protein TyrR were also identified through the use of such nucleoside analogs (239).…”
Section: Fluorescent Labelsmentioning
confidence: 99%